2022
DOI: 10.3389/fendo.2022.824215
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Diabetic Peripheral Neuropathy, Peripheral Artery Disease, and Foot Deformity Among the Population With Diabetes in Beijing, China: A Multicenter, Cross-Sectional Study

Abstract: Diabetic peripheral neuropathy (DPN), peripheral artery disease (PAD), and foot deformity are the most common causes of diabetic foot, which can considerably worsen the patient’s quality of life. In this study, we aimed to investigate the prevalence and risk factors associated with DPN, PAD, and foot deformity among patients with diabetes living in Beijing, China. In total, 3,898 diabetes patients from 11 hospitals in Beijing were evaluated using questionnaires and physical examinations, and 3,758 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…Pop-Busui et al 2 reported a 28% incidence of diabetic peripheral neuropathy in the United States, while the corresponding San Luis Valley cohort study 25 documented a slightly lower incidence rate of 25.8% for peripheral neuropathy. A cross-sectional study conducted in Beijing, China 26 revealed that peripheral neuropathy was present in 23.5% of individuals diagnosed with type 2 diabetes mellitus. The prevalence of type 2 diabetic peripheral neuropathy in the middle-aged and elderly population was found to be 35.6% in this study, which is significantly higher compared to previous research findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pop-Busui et al 2 reported a 28% incidence of diabetic peripheral neuropathy in the United States, while the corresponding San Luis Valley cohort study 25 documented a slightly lower incidence rate of 25.8% for peripheral neuropathy. A cross-sectional study conducted in Beijing, China 26 revealed that peripheral neuropathy was present in 23.5% of individuals diagnosed with type 2 diabetes mellitus. The prevalence of type 2 diabetic peripheral neuropathy in the middle-aged and elderly population was found to be 35.6% in this study, which is significantly higher compared to previous research findings.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have recognized that older age, longer DM duration, and worse glucose control are risk factors for DP. Meanwhile, obesity or overweight, worse renal function, unfavorable lipid profile (such as higher low-density lipoprotein cholesterol and lower high-density lipoprotein cholesterol), hypertension, and smoking are also associated with a higher risk of DPN (28,30,32,33,35,38). Notably, two studies reported that insulin treatment is associated with a higher risk of DPN (28,30).…”
Section: Risk Factors For Dpnmentioning
confidence: 99%
“…In addition, bacteria typically create biofilms that thwart immune clearance and encourage the development of antimicrobial resistance; in one research, 78.2% of chronic wounds exhibited biofilm creation. To guide the development of innovative therapies and inform antimicrobial therapy, a deeper comprehension of the microbiology of DFIs is crucial [22,23].…”
Section: Microbial Etiology Of Diabetic Foot Ulcermentioning
confidence: 99%